Efficacy of herbal medicine treatment based on syndrome differentiation for Parkinson’s disease: A systematic review and meta-analysis of randomized placebo-controlled clinical trials - Jun, Purumea; Zhao, HuiYan; Jung, In Chul; Kwon, Ojin; Han, Chang-Hyun; Won, Jiyoon; Jang, Jung-Hee (Frontiers in Pharmacology, 2023)
Background: Parkinson's disease (PD), the second most common progressive neurodegenerative disease, causes heterogeneous clinical symptoms. Patients experience a range of motor and non-motor symptoms, and personalized diagnosis and treatment are needed. In traditional East-Asian medicine, syndrome differentiation (SD) is a diagnostic approach for customized therapy that uses comprehensive analysis and varies for the same disease. We aimed to evaluate the efficacy of herbal medicine (HM) prescribed according to SD of PD. Methods: Ten electronic databases were searched from inception to August 2021 without language limitations. All randomized controlled trials (RCT) involving HM for SD of PD were included. Assessment of Cochrane's risk of bias and meta-analysis and Grading of Recommendations Assessment, Development, and Evaluation was also performed. Effect measurement were summarized using the mean difference (MD) with 95% CI, through a meta-analysis. Results: Thirteen RCTs involving 843 participants were included. The overall risk of bias was either low or unclear. Compared with the placebo, HM as combination therapy with Western medicine (WM) significantly improved the total Unified Parkinson’s Disease Rating Scale (UPDRS) (MD, -5.31 [95%CI, -8.17, -2.46]; P = 0.0003) and was more beneficial as assessed using UPDRS (I–III), Parkinson's Disease Questionnaire-39, and the Non-Motor Symptom Scale. Adverse events did not differ between the groups. Conclusion: The findings suggest that the treatment combined WM and HM based on SD diagnosis has additional benefits in PD treatment. However, the methodological quality of the included RCTs was suboptimal. Nevertheless, this systematic review is the first to investigate the efficacy of HM treatment according to the SD diagnosis in PD. The clinically meaningful improvement in HM according to SD in PD needs to be tested in further studies with rigorous designs and longer follow-up periods.